The benefits of corporate social responsibility introduction in small and medium-sized enterprises: a systematic review of the literature - Hodinková, Monika; Sadovský, Zdeněk (Business: Theory and Practice, 2016)
Corporate social responsibility is considered as an important part of entrepreneur’s strategic behaviour. Its purpose is not only to achieve and maintain the good economic results, but at the same time also effort to do well to the environmental and social impact of business on the society. The systematic review of the literature was used to compare attitude of domestic and foreign SMEs and to identify the benefits of CSRimplementation in business practice. The research findings point to the fact that the Czech SMEs do not realize enough the benefits of CSR introduction for their business.